Reasons for the seizure of cattle meat, their prevalence, and socio-economic impact in the Cotonou slaughterhouse - ANAGONOU, SESSIWEDE INGRID NADINE; ADENILE, D. Adam; DAGA, JUSTIN (My University, 2023)
The epidemiology of livestock diseases can be monitored through information received from slaughterhouses. The aim of this study is to evaluate the frequency of the reasons for the seizure of cattle meat and the economic and social impact of these seizures at the slaughterhouse of Cotonou from June to August 2021. Out of a total of 6,828 slaughtered cattle, partial seizures were made – 831 (12.17%). The organs frequently seized were the lungs (46.21%) and the liver (32.85%). Other organs seized were the heart, kidneys, and udders. Furthermore, after all the calculations, it was found that the seizures recorded during this year resulted in a total loss of around 7,625,000 XOF. These investigations were carried out in the Cotonou slaughterhouse, in order to contribute to the enrichment of the scientific sphere, but more importantly to be able to improve public health by identifying the dangers, and sources of diseases in humans.
Keywords: Seizure; Carcass; Cattle; Slaughterhouse; Economic impact